Tinjauan Kaidah Fiqih الضرر يزال Terhadap Praktik Thrifting Fashion Sebagai Perilaku Konsumsi Masyarakat Muslim di Era Modern - Nur Diana Khalida; Hanifah Fauziyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This article discusses the practical phenomenon of thrifting or buying and selling of goods, clothes and used objects that are of interest to people in this modern era. This study also discusses the review of fiqh rules regarding the harm that can be eliminated from the phenomenon of thrifting practices. The research method used in this study was library research and analyzed descriptively. Literature study or library research is research that uses related books or articles to collect data. The descriptive method is a step that is commonly used to analyze by describing the data that has been collected so that conclusions can be drawn. The results of the study explain that Thrifting or what is commonly referred to as secondhand is a way to extend the life of clothes by selling or buying used clothes that are still usable and without going through a redesign process. The practice of thrifting is allowed in Islam. This practice does have disadvantages but these disadvantages can be prevented and eliminated. So that this practice also has a positive impact in terms of the community's economy.